Model Konseling Psikoanalisa dengan Teknik Asosiasi Bebas untuk Meminimalisir Self Heteroseksual - Yunita, Nivea Vila; Suranata, Kadek; Suarni, Ni Ketut (Universitas Pendidikan Ganesha, 2019)
This study aims to determine the effectiveness of the implementation of psychoanalysis counseling with free association techniques to minimize self heteroseksual class VIII B in SMP Negeri 3 Singaraja. The research design used is Nonequivalent Control Group Design. Sampling of this research using intaq group with the number of members as much as 74 students, each divided into 37 students experimental group with 37 students control group. Analysis methods used were (1) Rasch analysis to transform logit scale data, (2) t-brunning to calculate the effectiveness of counseling model of psychoanalysis with free association technique, and (3) t-test to know the effect difference between psychoanalytic counseling model with guidance of classical counseling to heterosexuals in students. The results showed that (a) psychoanalysis counseling with effective free association technique to minimize heterosexual self with thitung > ttable (212,7 > 1,688), (b) There is difference of effectiveness of psychoanalytic counseling model heterosexual effect size 508,35 with guidance of classical counseling to efeect size 0,19Â Keywords: Rasch, Analysis, Associations, technique, Psychoanalysis, Counseling, Self Heterosexual